Standardized assessment of depression symptoms in post‐acute care: A screening threshold approach. Issue 4 (2nd March 2022) - Siconolfi, Daniel; Edelen, Maria O.; McMullen, Tara L.; Martino, Steven; Ahluwalia, Sangeeta C.; Chen, Emily K.; Dalton, Sarah E.; Paddock, Susan; Rodriguez, Anthony; Saliba, Debra; Mandl, Stella; Mota, Teresa
Abstract: Background: Depression symptoms have impacts on quality of life, rehabilitation and treatment adherence, and resource utilization among patients in post‐acute care (PAC) settings. The PHQ‐2 and PHQ‐9 are instruments for the assessment of depression, previously used in PAC settings, that have tradeoffs in terms of measurement depth versus respondent/assessor burden. Therefore, the present study tested a gateway version of the protocol (PHQ‐2 to 9). Methods: In 143 PAC settings in 14 U.S. markets across 10 states from November 2017 to August 2018, facility and research nurses administered the PHQ‐2 to communicative patients ( n  = 3010). Nurses administered the full PHQ‐9 if the patient screened positive for either of the two cardinal symptoms assessed by the PHQ‐2 (depressed mood and anhedonia). We assessed the prevalence and frequency of depression symptoms using the PHQ‐2 to 9, associations between depression screening results and patient characteristics and clinical conditions, and feasibility indicators. Results: More than 1 in 4 patients (28%) screened positive on the PHQ‐2. Only 6% of those completing the full PHQ‐9 had a score indicating "minimal" severity. The average score ( M  = 11.9) met the threshold for moderate depression. Positive PHQ‐2 screening was associated with age, female gender, disposition at discharge, septicemia/severe sepsis, and dependence for ADLs of toileting and lying to sitting mobility. Age was also associated with full PHQ‐9 scores; patients ages 45–64 had the highest mean score. Length of stay was not associated with PHQ‐2 screening results or full PHQ‐2 to 9 scores. Missing data were minimal (<2.4%). The average time to complete was 2.3 min. Interrater reliability and percent agreement were excellent. Conclusions: These findings suggest the feasibility of a gateway scoring approach to standardized assessment of depression symptoms among PAC patients, and that depression symptoms are relatively common among this inpatient population.